2018
DOI: 10.1111/jcmm.13564
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for Poria cocos mushroom polysaccharide used as an antitumour drug in China

Abstract: Poria cocos is an edible medicinal fungus known as “Fuling” in Chinese and has been used as a Chinese traditional medicine for more than two thousand years. Pharmacological studies reveal that polysaccharide is the most abundant substance in Poria cocos and has a wide range of biological activities including antitumour, immunomodulation, anti‐inflammation, antioxidation, anti‐ageing, antihepatitis, antidiabetics and anti‐haemorrhagic fever effects. As a result, “Poria cocos polysaccharide oral solution” was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 18 publications
1
67
0
Order By: Relevance
“…The relatively inexpensive polysaccharides from the traditional Chinese herbs should be useable for the development of novel therapeutic agents, functional food, or adjuvants for preventing or treating different pathological conditions as those fungal polysaccharide-based drugs approved and used in China. 6,[121][122][123][124][125][126]…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The relatively inexpensive polysaccharides from the traditional Chinese herbs should be useable for the development of novel therapeutic agents, functional food, or adjuvants for preventing or treating different pathological conditions as those fungal polysaccharide-based drugs approved and used in China. 6,[121][122][123][124][125][126]…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Poria cocos is a well-known medicinal mushroom and it possesses various pharmacological activities such as anti-tumor, anti-inflammatory, antioxidantive, diuretic, renoprotective and lipid-lowering effects ( Wang et al., 2013 ; Chen et al., 2019d ). Polysaccharide from Poria cocos not only has significant antioxidant stress scavenging ability of free radicals, but also can regulate the levels of IL-2 ( Li et al., 2019 ). Improving inflammatory environment is the embodiment of the theory of Whole View in IMN, but the relation of anti-inflammatory and the remission of IMN are just ignored in the research about herb medicine.…”
Section: The Research Direction Of Herb Medicine Treatment Imnmentioning
confidence: 99%
“…SGR invigorates the spleen and resolves phlegm, and it also calms the Heart and nerves. [58][59][60] Previous studies of SGR have shown that it can treat tumors, 61,62 improve depression, 63 relieve hyperglycemia and hyperlipidemia, 64 lessen insomnia, 65 and prevent dementia. 66 It also has potential therapeutic effects for leukemia.…”
Section: Smilax Glabra Roxbmentioning
confidence: 99%